2009
DOI: 10.1007/s10048-009-0171-7
|View full text |Cite
|
Sign up to set email alerts
|

Examination of association of genes in the serotonin system to autism

Abstract: Autism is characterized as one of the Pervasive Developmental Disorders (PDDs), a spectrum of often severe behavioral and cognitive disturbances of early development. The high heritability of autism has driven multiple efforts to identify genetic variation that increases autism susceptibility. Numerous studies have suggested that variation in peripheral and central metabolism of serotonin (5-HT) may play a role in the pathophysiology of autism. We screened 403 autism families for 45 SNPs in 10 serotonin pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 64 publications
(58 reference statements)
0
54
0
1
Order By: Relevance
“…In addition to the described genetic variations in SLC6A4, there are other gene variants that may have an additional effect or modest influence on autism risk. These include de novo copy number variations [26], serotonergic receptor single nucleotide polymorphisms such as in the HTR3A gene [27], and also other genetic variants (for a recent overview see [28]). Since the impact of these genetic variations remains unclear or inconclusive, we did not collect these data.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the described genetic variations in SLC6A4, there are other gene variants that may have an additional effect or modest influence on autism risk. These include de novo copy number variations [26], serotonergic receptor single nucleotide polymorphisms such as in the HTR3A gene [27], and also other genetic variants (for a recent overview see [28]). Since the impact of these genetic variations remains unclear or inconclusive, we did not collect these data.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous observations have revealed that the pathophysiology of ASD involves hyperserotonemia in up to 50% of individuals with ASD (with a concomitantly lower brain serotonin levels), thereby indicating that ASD associates with a distorted serotonergic distribution [49,[53][54][55]. Likewise, a circumstantial evidence in support of 5-HT involvement in autism is that defective brain serotonin levels are known to associate with many repetitive and aggressive behaviors like spinning, stepping, and self-hitting, that are common in ASD patients [56].…”
Section: Neurotransmitter Signalling and Implications In Asdmentioning
confidence: 99%
“…Several gene variants that may change the structure or function of the transporter protein are associated with autism. Variation within genes on the serotonin pathway, particularly HTR3A located on chromosome 11, were demonstrated modest effects on autism risk [58]. People with autism in France, Germany, Israel, Portugal, and the United States exhibited a preferential inheritance of SERT length polymorphism L variants [59].…”
Section: Neurotransmitter Systemmentioning
confidence: 99%